Militerisme Dalam Pemerintahan Sipil: Kajian terhadap Praktik Penyelenggaraan Pemerintahan - Dody Heryanto Sitorus; Ilham Agusyanda; M. Riezky Putra Pratama; Sonia Ivana Barus; Iskandar (PROGRESIF: Jurnal Hukum, 2026)
This study discusses key legal issues regarding the involvement of the military in government administration and its implications for democracy and the Indonesian constitutional system. Study aims to evaluate the massive involvement of the military in government, focusing on historical legacy as a basis. Research methods used are a normative approach and a historical approach.  Results of the study show the weak political will of the government to carry out one of the mandates of reform, namely to return the military to its role as a professional national defence force and to end military involvement in civil government affairs. This is evidenced by the massive deviation in the appointment of active TNI soldiers to civil positions in government, as these positions are not regulated in the TNI Law. Research findings indicate that there is still a lack of strict regulations limiting the types of civilian positions that can be filled by active-duty military personnel, as well as the absence of effective accountability and oversight mechanisms by civilian authorities over the process of filling these positions. Therefore, it is important to establish a new technical framework to limit the continuous expansion of the military's role into the civilian sphere.